Culturally Responsive Teaching in Science Education and its Relationship with Technopreneurship - Tanjung, Yul Ifda; Festiyed, Festiyed; Diliarosta, Skunda; Asrizal, Asrizal; Arsih, Fitri; Fadillah, Muhammad Aizri; Makrooni, Golaleh (Pandawan, 2025)
Culturally Responsive Teaching (CRT) has been widely recognized for its positive impact on teaching practices, yet its foundational concepts and relationship with students cultural backgrounds, diversity, and specific implementation in science education to foster technopreneurship remain underexplored. This study addresses this gap by systematically identifying and constructing the concept of CRT and its integration with technopreneurship in science education using the PRISMA systematic literature review method. Data were collected from reputable international and national journal articles published between 2018 and 2023. The findings reveal that CRT in science education serves as a framework for teaching that integrates students knowledge, experiences, cultural backgrounds, and environments with scientific methods while respecting individual diversity. Effective implementation requires teachers commitment and skills to create inclusive learning environments tailored to diverse student characteristics. Importantly, CRT inspires students to design technological innovations that address cultural challenges, thereby fostering entrepreneurial interest and capabilities. This study contributes novel insights into how CRT in science education bridges cultural understanding and technopreneurship development, offering a transformative approach to science teaching that aligns with global and local educational needs.